The factor affect leverage of listed construction companies / Muhammad Ikmal Hakim Saidun Bakri - Saidun Bakri, Muhammad Ikmal Hakim (Faculty of Business and Management, 2018)
In terms of leverage choice, the operation management and financial management of construction companies are very important. This is because failure to fulfil these will give impact to company's. It usually happen When there is bad financial management and lack of capital. According to Baharuddin, N. Khamis, Z., Wan Mahmood, W. M., and Dollah, H (201 1) defined that construction companies tend to use their own money first in settling the development before getting the profit. Therefore, there is a need to be explore and to investigate this issue. The purse of this study to examine affect the leverage of construction companies. This paper will focus on 20 construction firms that are listed in Bursa Malaysia. The dependent variable is leverage that Will be measure by debt to capital ratio. There are four independent variables in this study which is firm size, level of warrants, growth opportunities and cost of debt. The data from the sample of 20 construction companies and based on 5 year data from year 2009-2013. Total of 100 observations will be gained. This research will use quantitative secondary data which is panel data. Multiple regression model is use to interpret by the ordinary least squares (OLS) as the technique to determine the relationship between the dependent and independent variables.